Self-assessment and self-improvement as inclusive school development - Marianna Piccioli (Firenze University Press, 2022)
What are the strengths and weaknesses in the cultures, management policies and organizational practices that make an educational institution inclusive? This is the question we try to answer with this investigation, using the comparative element between the Italian and the Catalan school systems. This work is based on three theoretical frameworks: inclusive education in coherence with the Disability Studies approach; autonomy and leadership for inclusion and the self-evaluation and self-improvement processes as an inclusive school development in accordance with the perspective proposed by the Index for Inclusion. Field research reveals that the relevant legislation plays a crucial role and schools must regain a pedagogical thought in which organizational practices and management policies are based on inclusive cultural and value-based foundations.   Autovalutazione e automiglioramento come sviluppo inclusivo della scuola Quali sono i punti di forza e di debolezza nelle culture, nelle politiche gestionali e nelle pratiche organizzative che rendono inclusiva un'istituzione scolastica? Il contributo cerca di rispondere a questa domanda, anche attraverso la comparazione tra il sistema scolastico italiano e quello catalano, basandosi su tre quadri teorici: l'educazione inclusiva secondo l'approccio dei Disability Studies; l'autonomia e la leadership per l'inclusione; i processi di autovalutazione e automiglioramento come sviluppo inclusivo della scuola in relazione alla prospettiva proposta dall'Index for Inclusion. Dalla ricerca sul campo emerge che la legislazione di riferimento gioca un ruolo cruciale e la scuola deve riconquistare un pensiero pedagogico in cui pratiche organizzative e politiche di gestione siano fondate su basi culturali e valoriali inclusive.